Komunikasi Instruktif Nabi Muhammad SAW. Dalam Hadis: Landasan Dakwah Partisipatif bagi Pengembangan Masyarakat Islam Kontemporer - Ibrahim Baso, Andi Hadi; Nasir, St. Magfirah; Ilyas, Abustani (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines how the instructive communication of the Prophet Muhammad ﷺ recorded in the hadith can serve as a strategic model for participatory da'wah in the contemporary era, particularly from the perspective of Islamic Community Development. The Prophet's communicative principles educational, persuasive, dialogic, and humanistic hold significant relevance to the challenges of modern da'wah, which demand a more inclusive and transformative approach. Using a literature review method, this study explores the communicative values of the Prophet in authentic hadith and connects them to the principles of social participation that characterize the field of Islamic Community Development. The results of the study indicate that the Prophet's instructive communication emphasized active participation, respect for local culture, and empowerment of the community, all of which are key aspects in the process of sustainable Islamic community development.